Taktiken des Ego - Brockhaus, Christoph; Brüninghaus - Knubel, Cornelia; von Brücke, Dany; Dinkla, Söke; Friese, Peter; Groys, Boris; Heidt Heller, Renate; Meschede, Friedrich; Schmidbauer, Wolfgang; Schmidt, Eva; Schmidt Sabine Maria (Bielefield : Kerber Verlag, 2003)
Ahtila, Eija-Liisa; Barbier, Gilles; Brenner, Birgit; Davies, John; Emin, Tracey; Gerdes, Ludger; Ter Heijne, Mathilde; Liebscher, Martin; Manders, Mark; Mik, Aernout ; Muntean/Rosenblum ; Schnitt, Corinna ; Simpson, Lorna ; Vautier, Ben ; Viola, Bill
boek